O-021 Increased contrast enhancement of the parent vessel of unruptured intracranial aneurysms in 7T MR imaging. (4th August 2020) - Samaniego, E; Roa, J; Zhang, H; Koscik, T; Ortega-Gutierrez, S; Bathla, G; Sonka, M; Derdeyn, C; Magnotta, V; Hasan, D
Abstract : Background: Inflammation of the cerebral arterial wall may lead to aneurysm formation. The presence of aneurysm enhancement on high-resolution vessel wall imaging (HR-VWI) is a marker of wall inflammation and instability. We aim to determine if there is any association between increased contrast enhancement in the aneurysmal wall and its parent artery using 7T HR-VWI. Methods: Patients with unruptured intracranial aneurysms (UIAs) underwent 7T HR-VWI. Regions of interest were selected manually and with a semi-automated protocol based on gradient algorithms of intensity patterns. Mean signal intensities in pre- and post-contrast T1-weighted sequences were adjusted to the enhancement of the pituitary stalk and then subtracted to objectively determine: 1) circumferential aneurysmal wall enhancement (CAWE), 2) parent vessel enhancement (PVE), and 3) reference vessel enhancement (RVE). PVE was assessed over regions located 3- and 5-mm from the aneurysm's neck. RVE was assessed in arteries located in a different vascular territory. Results: Twenty-five UIAs were analyzed. There was a significant moderate correlation between CAWE and 5-mm PVE (Pearson R=0.52, P =0.008), whereas no correlation was found between CAWE and RVE (Pearson R=0.20, P =0.33). A stronger correlation was found between CAWE and 3-mm PVE (Pearson R=0.78, P <0.001). Intra-class correlation analysis demonstrated good reliability between measurements obtained using semi-automated and manual segmentation (ICC coefficient = 0.790, 95% CI 0.58 – 0.90). Conclusion: Parent arteries exhibit higher contrast enhancement in regions closer to the aneurysm's neck, especially in aneurysms ≥ 7 mm. A localized inflammatory/vasculopathic process in the wall of the parent artery may lead to aneurysm formation and growth. Disclosures: E. Samaniego: 1; C; SVIN 2019, Bee Foundation 2019. 2; C; Medtronic, MicroVention. J. Roa: None. H. Zhang: None. T. Koscik: None. S. Ortega-Gutierrez: 2; C; Stryker, MicroVention. G. Bathla: None. M. Sonka: None. C. Derdeyn: None. V. Magnotta: None. D. Hasan: None.